Accelerated curing of glued-in threaded rods by means of inductive heating – part II: modelling. Issue 3 (17th February 2021) - Ratsch, N.; Böhm, S.; Voß, M.; Adam, M.; Wirries, J.; Vallée, T.
ABSTRACT: The curing behaviour of inductively heated glued-in rods (GiR) experimentally tested in Part I of this work was further investigated with regard to the kinetics of adhesive curing, and evolution of strength with time. For that, dynamic DSC measurements were performed, and appropriate kinetic models were derived. These investigations were complemented with rheological experiments in which the adhesive were subjected to the same thermal regime as in the inductive heating of the GiR. Curing kinetics of the GiR were then compared to the increase of strength with time. The comparison showed that curing progress, defined by conversion degree, does not result in proportional strength increase. It was then attempted to estimate the influence of potential residual stresses from the induction curing on joint capacity. A relatively simple FE model was thus derived, which considered two different loading cases: a tensile force acting on the rod, and a shrinkage resulting from the induction process. Their superposition allowed for a general description of the fact that joint capacities increased with time elapsed since induction heating. Depending upon the adhesive considered, fair to very good quality of prediction were achieved.